A comparative study on learner's performance in the selected special undergraduate business programme of Open University Malaysia - Nur Azlin Omar; Chooi , Chea Chiam (2009)
The main challenge in Open Distance Learning (ODL) environment today is providing education to as many people as possible. Besides open market, Open University Malaysia (OUM) has introduced special market in living up to the life-long learning principles with its flexibility and self-managed learning. As its motto states, OUM is a ‘University for All: Opening Minds, Transforming Lives’, special market has the potential to add value of learning environment in open and distance learning. Programmes in the special market are designed in consultation with the sponsors of specific groups or organisations and may be delivered varies in length as needed. Army College (KTD) has enrolled at the special programme of Diploma in Management with OUM. This is a comparative study on KTD learners using two different batches between intakes of December 2007 and December 2008. The primary purposes of this study are: 1) to compare the learner’s performance between two different batches of KTD; and 2) to determine the impact of conducting different approach in teaching and learning system. The different approach of teaching and learning system is focused on daily learning hours, assessment format and the numbers of learner’s intake. Information or inputs for this study are gathered directly from final results from the learners. Observations on the learner’s results above are collected and analysed from two different batches based on different level of performance with high, medium and low. The outcome of this study will be useful to measure learner’s performance after changes in the approach of teaching and learning system. The final result of this study will be able to show the different approaches in influencing learner’s performance. Furthermore, recommendations will be proposed and suggested in hope for the business programme in special market to be further enhanced. It is also hoped that this study should inspire other researcher to explore the new approach of teaching and learning in ODL special market environment. (Authors' abstract)